An Ethnozoological Survey of the Sulawesi Water Rat (Waiomys mamasae): Insights from Local Communities, Gandang Dewata National Park - Fetranius Fetra; Muhammad Rizaldi Trias Jaya Putra Nurdin; Muh Rizal Kurniawan Yunus; Arlinda Puspita Sari; Maipa Dia Pati (Indonesian Journal of Ecology and Conservation, 2024)
This study aimed to explore population and condition data on the Sulawesi Water Rat (Waiomys mamasae) from an ethnozoological perspective in five buffer villages surrounding Gandang Dewata National Park. Using a cluster sampling technique, 66 respondents from various professions with direct interaction with river ecosystems were selected, including hunters, farmers, and other individuals frequently active in river areas. Data were collected through questionnaire-based interviews to obtain information regarding the frequency of sightings of this species and its utilization in local communities. The results showed that 50% of respondents had directly observed the Sulawesi Water Rat, while the rest had never encountered it. In terms of utilization, local communities use this species as a protective talisman to prevent house fires, as traditional medicine, and as a source of food. Several local beliefs also describe unique abilities of this species, such as the capacity to walk on water or remain submerged for extended periods. The age distribution of respondents was dominated by individuals aged 35–48 years (32%), followed by other age groups. This study provides important insights into local knowledge and the relationship between communities and W. mamasae, which can serve as an important basis for conservation efforts and ecosystem management in the buffer areas of Gandang Dewata National Park